Identification of the UDP-glucose-4-epimerase required for galactofuranose biosynthesis and galactose metabolism in A. niger - Park, Joohae (Fungal Biol Biotechnol, 2014)
BACKGROUND: Galactofuranose (Galf)-containing glycoconjugates are important to secure the integrity of the cell wall of filamentous fungi. Mutations that prevent the biosynthesis of Galf-containing molecules compromise cell wall integrity. In response to cell wall weakening, the cell wall integrity (CWI)-pathway is activated to reinforce the strength of the cell wall. Activation of CWI-pathway in Aspergillus niger is characterized by the specific induction of the agsA gene, which encodes a cell wall α-glucan synthase. RESULTS: In this study, we screened a collection of cell wall mutants with an induced expression of agsA for defects in Galf biosynthesis using a with anti-Galf antibody (L10). From this collection of mutants, we previously identified mutants in the UDP-galactopyranose mutase encoding gene (ugmA). Here, we have identified six additional UDP-galactopyranose mutase (ugmA) mutants and one mutant (named mutant #41) in an additional complementation group that displayed strongly reduced Galf-levels in the cell wall. By using a whole genome sequencing approach, 21 SNPs in coding regions were identified between mutant #41 and its parental strain which changed the amino acid sequence of the encoded proteins. One of these mutations was in gene An14g03820, which codes for a putative UDP-glucose-4-epimerase (UgeA). The A to G mutation in this gene causes an amino acid change of Asn to Asp at position 191 in the UgeA protein. Targeted deletion of ugeA resulted in an even more severe reduction of Galf in N-linked glucans, indicating that the UgeA protein in mutant #41 is partially active. The ugeA gene is also required for growth on galactose despite the presence of two UgeA homologs in the A. niger genome. CONCLUSION: By using a classical mutant screen and whole genome sequencing of a new Galf-deficient mutant, the UDP-glucose-4-epimerase gene (ugeA) has been identified. UgeA is required for the biosynthesis of Galf as well as for galactose metabolism in Aspergillus niger. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40694-014-0006-7) contains supplementary material, which is available to authorized users.